Mesna ameliorates acute lung injury induced by intestinal ischemia–reperfusion in rats - Samia Adel Abd El-Baset (Nature Portfolio, 2021)
Abstract The lung is severely affected by intestinal ischemia–reperfusion (I–R) injury. Mesna, a thiol compound, possess anti-inflammatory and antioxidant properties. We aimed in the present work to explore the potential beneficial effects of Mesna on the acute lung damage mediated by intestinal I–R in a rat model. Forty male adult albino rats were randomly separated into; control, intestinal I–R, Mesna I and Mesna II groups. Mesna was administered by intraperitoneal injection at a dose of 100 mg/kg, 60 min before ischemia (Mesna I) and after reperfusion (Mesna II). Arterial blood gases and total proteins in bronchoalveolar lavage (BAL) were measured. Lung tissue homogenates were utilized for biochemical assays of proinflammatory cytokines and oxidative stress markers. Lung specimens were managed for examination by light and electron microscopy. Our results revealed that Mesna attenuated the histopathological changes and apoptosis of the lung following intestinal I–R. Mesna also recovered systemic oxygenation. Mesna suppressed neutrophil infiltration (as endorsed by the reduction in MPO level), reduced ICAM-1 mRNA expression, inhibited NF-κB pathway and reduced the proinflammatory cytokines (TNF-α, IL-1β and IL-6) in the lung tissues. Mesna maintained the antioxidant profile as evidenced by the elevation of the tissue GPx and SOD and down-regulation of HSP70 immune-expressions. Accordingly, Mesna treatment can be a promising way to counteract remote injury of the lung resulted from intestinal I–R.